Pengaruh Intelegensi terhadap Prestasi Akademik Taruna dalam Simulasi Kehidupan Kapal di Kampus BP2IP Tangerang - Ratna Ika Setiyaningish, Untari (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2019)
This research aims to determine the correlation among the intelligence and the academic achievement of the Cadet in the life of ship simulation on campus BP2IP Tangerang. This research is a quantitative study with Taruna BP2IP Tangerang as the sample of the research. By using random sampling technique. Data collection is using surveys. Data analysis is using a Likert scale.The results of the research show that there is a partial direct positive influence on the intelligence of Taruna's academic achievement in the life simulation of the ship at BP2IP Tangerang Campus.